Antioxidant and Hypolipidemic Activities of Acid-Depolymerised Exopolysaccharides by Termitomyces albuminosus. (8th September 2019) - Zhao, Huajie; Wang, Xiuxiu; Liu, Xinchao; Zhang, Jianjun; Wan, Luzhang; Jia, Le
Abstract : The acid-depolymerised exopolysaccharides (ADES) of Termitomyces albuminosus were obtained, and the major fraction of ADES1 was isolated and purified by DEAE-52 cellulose anion-exchange column chromatography. Physicochemical characterizations showed that ADES1 was an α - and a β -configuration with the molecular weight of 2.43 kDa, containing (1→3, 4)-linked-Glc p, (1→4)-linked-D-Glc p, (1→3)-linked-D-Xyl p, (1→4)-linked-D-Man p, T-Glc p, (1→6)-linked-D-Gal p, and (1→4)-linked-L-Ara p . The in vivo assays showed that ADES1 could reduce lipid levels in the serum and liver, decrease serum enzyme activities, and improve antioxidant enzyme activities and p-AMPK α expressions in hyperlipidemic mice, which were also confirmed by histopathological observations. These data indicated that ADES1 might be considered as a novel substance to treat and prevent hyperlipidemia and as a hepatoprotective agent.